PROSES PELAKSANAAN DANA DESA DI DESA PONGGOK KECAMATAN POLANHARJO KABUPATEN KLATEN - Kein, Asriel; Harsasto, Priyatno (Journal of Politic and Government Studies, 2018)
Village funds are one of the priority government policies to finance development and empowerment of communities whose implementation is prioritized on a self-managed basis using local resources or raw materials, and strived to absorb more local people's labor. This study aims to determine the process of implementation of village funds used in accordance with the program, the results of the implementation of village funds and community involvement in the Village District Ponggok Polanharjo Klaten. The research approach used is descriptive qualitative. Using data collection techniques through interviews to informants that are considered potentially to provide information about the process of implementing village funds in the development of Ponggok Village, Polanharjo Sub-district, Klaten Regency, also through interviews and documentation of the results of the implementation of village funds. The research results indicate that the process of implementation of village funds is done well and in accordance with the needs of Ponggok village community. This can be evidenced by the number of development programs that have been realized in accordance with the development plan that has been established by the village government through village meetings. From the results of 18 (eighteen) development activities that have been planned all the time has been realized with 15 (fifteen) physical activities in the form of suggestions and services and 2 (two) community empowerment and 1 (one) community development, although not yet realized the name of the community who know that the government villages prioritize village funds for physical development and community empowerment, in accordance with the results of village meetings. However,development activities in this case physical development in the form of suggestions and prasanan and community empowerment realized well. The conclusion of the implementation of village funds by the village government of Ponggok shows that the Implementation of Village Funds in the Development of Ponggok Village, Polanharjo Sub-district, Klaten Regency is said to be effective. Due to the involvement of the community in the implementation of village funds in Ponggok Village, where the community has been involved in the preparation of the development plan until the implementation of the programs.Keywords: Village Funding, Implementation, Involvement